Tetraspanin CD37 contributes to the initiation of cellular immunity by promoting dendritic cell migration. - Gartlan, K; Wee, J; Demaria, M; Nastovska, R; Chang, T; Jones, E; Apostolopoulos, V; Pietersz, G; Hickey, M; van Spriel, AB; Wright, MD (2013)
Previous studies on the role of the tetraspanin CD37 in cellular immunity appear contradictory. In vitro approaches indicate a negative regulatory role, whereas in vivo studies suggest that CD37 is necessary for optimal cellular responses. To resolve this discrepancy, we studied the adaptive cellular immune responses of CD37(-/-) mice to intradermal challenge with either tumors or model antigens and found that CD37 is essential for optimal cell-mediated immunity. We provide evidence that an increased susceptibility to tumors observed in CD37(-/-) mice coincides with a striking failure to induce antigen-specific IFN-γ-secreting T cells. We also show that CD37 ablation impairs several aspects of DC function including: in vivo migration from skin to draining lymph nodes; chemo-tactic migration; integrin-mediated adhesion under flow; the ability to spread and form actin protrusions and in vivo priming of adoptively transferred naïve T cells. In addition, multiphoton microscopy-based assessment of dermal DC migration demonstrated a reduced rate of migration and increased randomness of DC migration in CD37(-/-) mice. Together, these studies are consistent with a model in which the cellular defect that underlies poor cellular immune induction in CD37(-/-) mice is impaired DC migration.